Information and Communications Technology in Chemistry Education - Pernaa, Johannes (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
This article looks at the possibilities of Information and communications technology (ICT), which is also central in supporting teaching and learning of chemistry. It is also vital in promoting sustainable development. ICT is a general concept, under which all different media and technologies can be placed, which can be used as support in data processing. The topic is quite broad and needs demarcation. The theory of blended learning can be used here, which is one of ICT’s theory frames that models the possibilities of using them in teaching (see Pernaa & Aksela, 2013). In order to support pondering, examples and recommendations of software are presented, which the teachers’ can exploit in teaching. This article is partly based on Johannes Pernaa’s doctoral dissertation, which was completed in 2011 (Pernaa, 2011), where it was researched, how ICT-based chemistry learning environments are developed based on research. The developing of learning environments based on research is an important standpoint in the topic, which is why we look at it more closely at the end of this article. Watch video preview of article: https://youtu.be/U0tPCKWzWco